Інституційний механізм спільної зовнішньої політики Європейського Союзу - Конончук, І.; Kononchuk, I. (Східноєвропейський національний університет імені Лесі Українки, 2019)
У статті проаналізовано акти первинного й вторинного права, які регулюють інституційний механізм спільної зовнішньої політики Європейського Союзу (далі – ЄС). Досліджено правовий статус та повноваження інституцій ЄС у сфері спільної зовнішньої політики й політики безпеки. Визначено зміни у сфері спільної зовнішньої політики та політики безпеки ЄС після набрання чинності Лісабонського договору. Висвітлено питання розподілу повноважень між інституціями ЄС. З’ясовано особливості функціонування інституційного механізму в рамках співпраці держав-членів у сфері спільної зовнішньої політики та політики безпеки. The article analyzes the acts of primary and secondary law governing the institutional mechanism of the joint foreign policy of the European Union (hereinafter - the EU). In the focus of the research are the legal status and powers of the EU institutions in the domain of joint foreign and security policy. The emphasis is laid on the changes in the joint foreign and security policy of the EU, introduced since the Lisbon Treaty came into force. The study has revealed that both the main EU institutions (European Council, Council, European Commission, the European Parliament) and the system of special bodies (High Representative of the Union for Foreign Affairs and Security Policy, European External Action Service, the Political and Security Committee and CFSP Working Groups) are empowered to implement Common Foreign and Security Policy. The key findings of the study elucidate the features of the powers division between EU institutions and the peculiarities of the institutional mechanism functioning in the framework of the Member States cooperation in the field of common foreign and security policy.
Institutional Mechanisms of European Union Foreign Policy
Keywords: спільна зовнішня політики та політика безпеки; Європейський Союз; Верховний представник Союзу із зовнішніх справ та політики безпеки; Європейська служба зовнішньополітичної діяльності; Комітет з питань політики та безпеки; Common Foreign and Security Policy; European Union; High Representative of the Union for Foreign Affairs and Security Policy; European External Action Service; Political and Security Committee